Peran Penyuluh Kehutanan Swadaya Masyarakat (PKSM) dalam Membantu Masyarakat Mendapatkan Izin Hutan Kemasyarakatan (HKm) di Kecamatan Sendang Agung Kabupaten Lampung Tengah - Fadila Ayu Larasati; Rommy Qurniati; Susni Herwanti (Jurnal Ilmu Pertanian Indonesia, 2015)
One of the solutions to increase the community welfare and manage the forest is by giving the Social Forestry license. The implementation of community forest intend to give space for the local community for sustainable forest management. The submission of HKm license was done by farmers of HKm group who already received facilitaties from forestry partner that is Non-govermental Forestry Extension Worker (PKSM) to regent. The objectives of this research were to analyze the role of PKSM level for assisting farmer to obtain HKm license and analyze the correlation between external and internal factors of partner with their role. This research was done in Subdistrict Sendang Agung as an area under the jurisdiction of PKSM to assist submission of HKm license. The data was analized by Chi Square test, meanwhile to detect the correlation level of respondent factors with partner role is using coefficient contingency correlation analize. Based on analize result partner role level is obtained in high classification, partner role is as dynamist, mediator, facilitator, motivator, and educators. Internal factors companion that has a strong enough relationship with the role of companion is the number of dependents, long-serving, and cosmopilitaness, where as age, income, as well as information disclosure had uneasy relations. External factors companion that has a strong relationship with the companion role is recognition of the success and intensity of supervision, facilities have less close relationship level with the role of companion.